2022
DOI: 10.1002/jcc.26940
|View full text |Cite
|
Sign up to set email alerts
|

Protein–ligand binding affinity prediction of cyclin‐dependent kinase‐2 inhibitors by dynamically averaged fragment molecular orbital‐based interaction energy

Abstract: Fragment molecular orbital (FMO) method is a powerful computational tool for structure-based drug design, in which protein-ligand interactions can be described by the inter-fragment interaction energy (IFIE) and its pair interaction energy decomposition analysis (PIEDA). Here, we introduced a dynamically averaged (DA) FMO-based approach in which molecular dynamics simulations were used to generate multiple protein-ligand complex structures for FMO calculations. To assess this approach, we examined the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…In addition, ensitrelvir attractively interacts with Thr24 (Thr25 fragment), Thr25, Thr26 (itself and Leu27 fragments), Met49, Phe140 (Leu141 fragment), Asn142, Ser144, Cys145, Met165, Glu166, Gln189, and five bridging waters. From the short MD simulation, we have confirmed that the inhibitor binding pose is stable to some extent compared with the X-ray crystal structures, while it might be even better to evaluate it with dynamically averaged FMO-based IFIE analysis using the MD snapshot structures . We have registered the FMO calculation data of M pro and inhibitor complexes published in PDB to the FMODB, , and the data are made available to SBDD for researchers worldwide.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, ensitrelvir attractively interacts with Thr24 (Thr25 fragment), Thr25, Thr26 (itself and Leu27 fragments), Met49, Phe140 (Leu141 fragment), Asn142, Ser144, Cys145, Met165, Glu166, Gln189, and five bridging waters. From the short MD simulation, we have confirmed that the inhibitor binding pose is stable to some extent compared with the X-ray crystal structures, while it might be even better to evaluate it with dynamically averaged FMO-based IFIE analysis using the MD snapshot structures . We have registered the FMO calculation data of M pro and inhibitor complexes published in PDB to the FMODB, , and the data are made available to SBDD for researchers worldwide.…”
Section: Discussionmentioning
confidence: 72%
“…From the short MD simulation, we have confirmed that the inhibitor binding pose is stable to some extent compared with the X-ray crystal structures, while it might be even better to evaluate it with dynamically averaged FMO-based IFIE analysis using the MD snapshot structures. 41 We have registered the FMO calculation data of M pro and inhibitor complexes published in PDB to the FMODB, 27,29 and the data are made available to SBDD for researchers worldwide. These findings are expected to provide creative insights for further improvement of inhibitory potency against M pro and help develop novel inhibitors with SBDD.…”
mentioning
confidence: 99%
“…One limitation of performing FMO calculations in the gas phase, as performed in this study, is that the binding affinities of ligands with different net charges cannot be predicted. To overcome this limitation, we are currently testing more theoretically sophisticated approaches, such as the FMO-based Poisson–Boltzmann surface area , and the dynamically averaged FMO approach . Here, we conclude that rational design of RNA binders is possible using FMO, especially after establishing structure–activity relationships.…”
Section: Discussionmentioning
confidence: 93%
“…The partition analysis (PA), as implemented in GAMESS, allows us to circumvent this “inconvenience” by allowing arbitrary monomer definitions (called segments in PA to differentiate them from fragments). The FMO method, in its many flavors, was successfully used to gain insight into complex biomolecular systems. The choice of DFTB in our work is motivated by the availability of PA only in combination with this self-consistent field (SCF) method. Nevertheless, as recent works show, it may be an appropriate tool for our needs. , Unless indicated differently, all data discussed in this work is from PA based on FMO2-DFTB3/PCM/D3­(BJ)/3ob calculations.…”
Section: Methodsmentioning
confidence: 99%